Credit Default Swaps Mechanics and Empirical Evidence on Benefits, Costs, and Inter-Market Relations - Culp, Christopher L. (Palgrave Studies in Risk and Insurance, 2018)
This book, unique in its composition, reviews the academic empirical literature on how CDSs actually work in practice, including during distressed times of market crises. It also discusses the mechanics of single-name and index CDSs, the theoretical costs and benefits of CDSs, as well as comprehensively summarizes the empirical evidence on important aspects of these instruments of risk transfer. Full-time academics, researchers at financial institutions, and students will benefit from the dispassionate and comprehensive summary of the academic literature; they can read this book instead of identifying, collecting, and reading the hundreds of academic articles on the important subject of credit risk transfer using derivatives and benefit from the synthesis of the literature provided.